2022
DOI: 10.7150/jca.71894
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase 2 Promotes Cell Proliferation and Tumor Formation through the Wnt/β-catenin Pathway-mediated Cyclin D1/c-myc Upregulation in Epithelial Ovarian Cancer

Abstract: Background: HK2 is reported as a key mediator of aerobic glycolysis, associating with the malignant growth in many types of cancers. Methods: In this study, stimulation of HK2 expression was observed in ovarian carcinoma tissues, comparing with the normal ovarian tissues. Results: Both of in vitro and in vivo experiments demonstrated that HK2 expression promoted the proliferation and tumor formation by acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…In general, activation of the Wnt/β-catenin signaling pathway induces transcription of genes associated with cell proliferation . It has been shown that Gln deficiency leads to impairment of the Wnt/β-catenin pathway and diminished protein synthesis, thereby affecting the growth of oligodendrocytes, which is similar to our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, activation of the Wnt/β-catenin signaling pathway induces transcription of genes associated with cell proliferation . It has been shown that Gln deficiency leads to impairment of the Wnt/β-catenin pathway and diminished protein synthesis, thereby affecting the growth of oligodendrocytes, which is similar to our results.…”
Section: Discussionsupporting
confidence: 91%
“…In general, activation of the Wnt/β-catenin signaling pathway induces transcription of genes associated with cell proliferation. 40 It has been shown that Gln deficiency leads to impairment of the Wnt/β-catenin pathway and diminished protein synthesis, thereby affecting the growth of oligodendrocytes, 16 which is similar to our results. Gln evidently enhanced the expression of β-catenin, active-β-catenin, TCF4, c-Myc, and cyclin D1, thus waking the Wnt/β-catenin pathway in IPEC-J2 cells.…”
Section: ■ Discussionsupporting
confidence: 90%
“…The Immunohistochemistry used in this study were performed as previously described [ 31 ]. The staining intensity was scored as: 0 (no staining), 1 (light brown), 2 (brown), 3 (dark brown).…”
Section: Methodsmentioning
confidence: 99%
“…Oncogenic signaling pathways, such as phosphoinositide 3-kinase (PI3K)/AKT, Myc, and the Hippo pathway mediated upregulation and hyperactivation of metabolism-related genes [ 70 ]. K-Ras and c-Myc are responsible for increased glycolysis [ 71 , 72 ]. PIK3CA and ubiquitin-specific peptidase 13 (USP13) genes have been reported to be co-amplified in about 30% of HGSC [ 73 ].…”
Section: Resultsmentioning
confidence: 99%